New Cylindrocladiella spp. from Thailand soils - L. Lombard (2018)
© Guizhou Academy of Agricultural Sciences Abstract Species of Cylindrocladiella (Nectriaceae) are generally regarded as saprobes or weak plant pathogens, typically causing problems in nurseries under high humidity conditions. Although the genus Cylindrocladiella is a common soil inhabitant in tropical and subtropical countries, only seven species have thus far been reported from Thailand. The aim of this study was thus to investigate various soil samples from northern Thailand for the presence of Cylindrocladiella, and to identify isolates to species level using a combination of cultural studies, morphology and DNA phylogeny (ITS, tef1 and tub2 gene regions). From the various isolates obtained, six new Cylindrocladiella species could be identified, described here as C. brevistipitata, C. horticola, C. humicola, C. lateralis, C. reginae, and C. terrestris. Further studies are required to establish the ecology of the new species, and also to determine which potential species occur in other as yet unsampled regions in Thailand.